STUDI KOMPARATIF ILMU HADITS DALAM MAZHAB SUNNI DAN SYI’AH - Ahiel Ahdi Besari (Jurnal Pendidikan Agama Islam, 2025)
The science of hadith has a key position in the development of Islamic teachings. The Sunni and Shia schools have created different ways of studying hadith, reflecting theological and historical differences. This paper discusses by comparing the basic principles of the science of hadith in both schools, especially related to the criticism of sanad, the validity of narrators, and the compilation of hadith books. Using a qualitative method based on literature study, this study analyzes important works such asSahih Al-Bukhari And Al-Kafī. The findings of the study show that although there are similarities in the structure of narrative criticism, there are significant differences in the authority of the companions, the emphasis on the Ahlul Bait, and the way the hadith is validated. This study opens up opportunities for a more open cross-school understanding in the study of modern Islamic science.